Removal of Nickel(II) from Wastewater: Activated Carbons from Oilcakes - Hema, M.; Srinivasan, K. (Asian Journal of Chemistry, 2010)
Activated carbons prepared from agro industrial waste by products such as coconut and neem oilcake, by thermal activation at 800 ºC, were used as efficient sorbents for the removal of nickel ion from wastewater. The sorption conditions, such as pH, adsorbent dose and concentration of nickel(II) were examined. The coconut oilcake activated carbon (COCAC) shows more adsorption efficiency than neem oilcake activated carbon (NOCAC). The kinetic processes of Ni(II) adsorption on to activated carbons were described by applying pseudo-first-order, pseudo-second- order and reversible pseudo-first-order rate equations. The kinetic data was found to follow pseudo-second-order rate equation for both carbons. The equilibrium data were studied by Freundlich, Langmuir and Temkin isotherm. Based on regression coefficient, Temkin isotherm model was found to be more suitable for these carbons.